Phylogenetic evidence for nationwide expansion Brucella melitensis lineages drives the re-emerging and epidemic of human brucellosis in Jiangsu, China - Wang, Weixiang; Lu, Zhou; Teng, Ge; Yan, Zikang; Huang, Lan; Tan, Zhongming; Liu, Zhiguo; Ding, Songning; Li, Zhenjun (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveHuman brucellosis has re-emerged as a major public health threat in Jiangsu Province, but the sources and transmission dynamics of circulating strains remain poorly understood.MethodsIn this study, we integrated conventional biotyping, whole-genome sequencing single-nucleotide polymorphism (WGS-SNP) analysis, and core genome multilocus sequence typing (cgMLST) to investigate the phylogenetic relationships of Brucella melitensis in the region.ResultsAmong 89 isolates analyzed, all were confirmed as B. melitensis (16 as biovar 1 and 73 as biovar 3), with a widespread geographic distribution across 15 cities in Jiangsu and adjacent areas, indicating extensive regional dissemination. All strains belonged to sequence type 8 (ST8) and genotype group II, clustering within the East Mediterranean lineage. Genomic resolution classified these strains into five SNP clades (C-I to C-V) and 17 SNP-based genotypes (STs), revealing a ladder-like phylogenetic structure. The lack of distinct geographic clustering suggests frequent cross-regional transmission, likely facilitated by the movement of infected sheep and goats. Phylogenomic analysis through cgMLST revealed distinct clustering of the 17 STs into two major groups (G-I and G-II), with 15 STs (88.2%) showing high genetic concordance between Jiangsu isolates and strains from China’s northeastern and northwestern. This compelling genomic evidence establishes that the current human brucellosis epidemic in Jiangsu is being driven by the nationwide expansion of dominant B. melitensis lineages.ConclusionThe findings provide crucial insights into the infection sources and interregional transmission dynamics of brucellosis in southern China, highlighting the significant role of domestic animal movement in pathogen dissemination, demanding coordinated cross-regional interventions including strict implementing intervention strategies and enhance disease surveillance.